Performance Analysis of Initial Public Offerings (IPO) in Indian Capital Market-An Empirical Study - Soundarapandlyan , K.; Ganesh , M. (Gyan Management Journal, 2014)
The main reason for IPOs is the need for fresh capital to finance various business activities, such as the development of new products or expansion into new markets. IPOs are considered to be risky for both the issuers and the investors. Therefore, an initial public offering is a transformational event for an organization. Investing in !PO has its own set of advantages and disadvantages. The present study is conducted to analyze the Performance of /PO in the Indian capital market for some years. The performance of /PO was analyzed with the help of issue price and last traded price and the same was helpful for the firm to find out the profitable issues from the total issues made during the period. It provides an insight for an investor' to make better investment decision in the volatile market conditions. The primary objectives chosen in the study are: Total funds mobilized through /PO in the Indian Capital Market for certain sectors, significant number of issues passed, their returns and their average listing across the sectors and to find out if there is a correlation between GDP Rate, Inflation, NIFTY Returns and /PO Returns. The entire study covers the /PO issued by various companies in India. Thus the study helps to create the awareness in the minds of the investor regarding the future prospects of the Company and their likely returns in the near future to help the investor in making better investment decisions.
Keywords: IPOs; Issue Price; Traded Price; Funds Mobilized; GDP Rate; Inflation; NIFTY Returns; Future Prospects